Methicillin-resistant Staphylococcus aureus (MRSA) isolated from pet animals and pet and non-pet owners - Abdul Aziz, Saleha; M., Shamzarina; Othman, Fauziah; Zakaria, Zunita (Veterinary Association Malaysia, 2006)
This study was done to determine the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) among cats and dogs, the pet owners and in persons who did not keep pets and to determine the antibiotic susceptibility of the isolates. MRSA was isolated from 7 (11.7%),18 (30%) and 8 (13.3%) of the 60 samples each collected from 30 cats and dogs, 30 pet owners and 30 persons who did not keep pets respectively. Twenty percent (6/30) of the cats and dogs, 30% (9/30) of pet owners and 20% (8/30) of persons who did not keep pets were positive for MRSA. The S. aureus isolates showed resistance to four other antibiotics, namely ampicillin, erythromycin, tetracycline and streptomycin; all isolates were sensitive to gentamicin. The zoonotic and anthroponotic potentials of MRSA in animals were reviewed.